NILAI–NILAI PENDIDIKAN DALAM SENI KALIGRAFI KARYA SYAIFUL ADNAN - Maryono (Wahana Islamika: Jurnal Studi Keislaman, 2018)
As one of the works of art, Islamic calligraphy is one medium ofda'wah because it contains the value of the investigation.Therefore the purpose of this research is to know the values ofeducation in Calligraphy Art in Serambi Seni Syaiful AdnanYogyakarta. In order to realize the purpose of research, thisresearch uses the method as well. Data analysis techniquesresearchers classify key words, create categories, formulate themesand integrate the results of analysis into depskriptif form. Theresults of the study found that Syaiful's work after havingobserved the values of education is mainly related to thepsychological phenomena of Islamic education related to Islamiccalligraphy, the basic values of art are the value of the content, thevalue of knowledge, the value of ideas, and the value of themessage on the value of oral, aesthetic education. Calligraphyartworks Syaiful Adnan of the characters, colors, very determinethe message and affect the attitude and nature for the Islamiceducation, psychology.